A comparative study of the use of layered double hydroxides (LDHs) and zeolite to reduce nitrate leaching in greenhouse maize farming. (21st October 2022) - Talebi, Nasrollah; Mohammadi Torkashvand, Ali; Pazira, Ebrahim; Esfandiari, Mehrdad
Abstract: The use of Layered Double Hydroxides (LDHs) and zeolite to reduce nitrate leaching in greenhouse maize farming was investigated. A research was conducted using a completely randomized factorial design experiment with 5 different treatments of zeolite and LDH application, 3 treatments of LDH (4, 8 and 16 g LDH per kg of soil), 1 zeolite treatment (16 g zeolite per kg of soil), 2 amounts of nitrate fertilizer with urea source (150 and 300 kg urea per hectare), 2 urea fertilizer installments with the control sample. In this research, the irrigation was repeated four times to collect the effluent. The results showed that the highest concentration of nitrate output in effluent was related to treatments without LDH and zeolite, and the lowest level was obtained with 16 g LDH kg −1 soil treatment. Using 16 g LDH kg −1 soil reduced N-nitrate leaching loss by up to 75% compared to the control sample. Comparison of using 16 g LDH kg −1 soil with 16 g zeolite kg −1 soil showed that LDH has a much higher ability to absorb nitrate from soil and prevent its leaching. Such that the lowest amount of LDH, 4 g LDH kg −1 soil, had more impact on mean reduction of effluent's nitrate concentration compared to 16 g zeolite kg −1 soil. With increasing the use of LDH and two-installment application of fertilizer increased the number of green leaves and biological yield.